Providing negative cost public projects under a fair mechanism: An experimental analysis - Werner Güth; Anastasios Koukoumelis; M. Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
This paper experimentally examines a procedurally fair provision mechanism allowing members of a small community to determine, via their bids, which of four alternative public projects to implement. Previous experiments with positive cost projects have demonstrated that the mechanism is efficiency enhancing. Our experiment tests whether the mechanism remains conducive to efficiency when negative cost, but less efficient, projects are made available. We find that this is not the case. On the other hand, we detect no significant difference in bid levels depending on whether mixed feelings are present or absent, and on whether the others valuations are known or unknown.
Keywords: C72; C92; D63; H44; 330; bidding behavior; experiment; procedural fairness; public projects